2007
DOI: 10.1159/000101067
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Complexity and Social Organization Sculpt the Brain in Lake Tanganyikan Cichlid Fish

Abstract: Complex brains and behaviors have occurred repeatedly within vertebrate classes throughout evolution. What adaptive pressures drive such changes? Both environmental and social features have been implicated in the expansion of select brain structures, particularly the telencephalon. East African cichlid fishes provide a superb opportunity to analyze the social and ecological correlates of neural phenotypes and their evolution. As a result of rapid, recent, and repeated radiations, there are hundreds of closely-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
376
5
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(401 citation statements)
references
References 148 publications
19
376
5
1
Order By: Relevance
“…Habitat has also been shown to influence brain size in bats (Safi & Dechmann 2005) and, in Tanganyikan cichlids, habitat complexity was found to be associated with larger brains and larger cerebella, while the telencephalon showed a similar trend (Pollen et al 2007). Habitat complexity was further shown to be correlated with the number of species and number of individuals (Pollen et al 2007); however, we found that habitat and diet are correlated, but Pollen et al (2007) did not include diet in their analyses, thus its influence on brain size cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Habitat has also been shown to influence brain size in bats (Safi & Dechmann 2005) and, in Tanganyikan cichlids, habitat complexity was found to be associated with larger brains and larger cerebella, while the telencephalon showed a similar trend (Pollen et al 2007). Habitat complexity was further shown to be correlated with the number of species and number of individuals (Pollen et al 2007); however, we found that habitat and diet are correlated, but Pollen et al (2007) did not include diet in their analyses, thus its influence on brain size cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…bottom-dwelling invertebrates and crustaceans) as 3; plankton and zooplankton as 4; invertebrates and crustaceans found in the water column as 5; and fishes as 6. Habitat reflected variation in complexity, previously shown to be correlated with brain structure (Pollen et al 2007): benthic and benthopelagic habitats were coded as 1; semi-pelagic as 2; sandy or shallow vegetated habitats as 3; rocky or rubble as 4; and rock habitat as 5. Pollen et al (2007) showed that sandy, rocky or rubble (intermediate) and rock habitat differ significantly in several quantitative measures of complexity, thus the categorization adequately reflects complexity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various species of reef fish have larvae that navigate through multiple coastal ecosystems before settling (Nagelkerken 2009). For example, reef species that are associated with mangroves and seagrass beds during only their early life stage need to navigate as larvae from the open ocean, across coastal shelves that harbor coral reefs, towards bays or lagoons that harbor juvenile habitats (Pollen et al 2007, Pollux et al 2007. Potentially, larvae of such species consecutively use auditory, olfactory, and visual cues to navigate from the open ocean towards their settlement habitats (Huijbers et al 2012).…”
Section: Introductionmentioning
confidence: 99%